2010
DOI: 10.1345/aph.1p251
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of the Surviving Sepsis Campaign Treatment Guidelines on Clinical Outcomes in a Community Hospital

Abstract: Implementation of a 2-part sepsis bundle based on the Surviving Sepsis Campaign Guidelines can yield a positive impact on clinical outcome and mortality in a nonacademic, community hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…Other observational and quasiexperimental studies reported similar results (40,55,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). When EGDT was incorporated into a clinical pathway for the treatment of severe sepsis and septic shock, hospital mortality could be decreased (93).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlementioning
confidence: 61%
“…Other observational and quasiexperimental studies reported similar results (40,55,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). When EGDT was incorporated into a clinical pathway for the treatment of severe sepsis and septic shock, hospital mortality could be decreased (93).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlementioning
confidence: 61%
“…[7] reported that the mortality in the compliant group decreased from 49% to 23% ( p = 0.01), compared with the non-compliant group. Mortality was 61.1% in the non-bundle group versus 20% with the bundle ( p < 0.001) [15]. Delivery of the interventions had an association with reduced mortality: for the sepsis six, 20.0% compared with 44.1% ( p < 0.001); for the resuscitation bundle, 5.9% compared with 51% ( p < 0.001) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The recent development and implementation of international guidelines for management of severe sepsis and septic shock or multidisciplinary care in the intensive care unit (ICU) might decrease the incidence of mortality that was observed in complicated PUDs until 2004 [20,21]. The relatively low number of gastric procedures performed in western countries, compared with Japan, might not enable western clinicians to undertake a community-based study such as ours [22].…”
Section: Discussionmentioning
confidence: 99%